G31(P) Comparison of antibiotic prescribing patterns between General Practitioner and Paediatric trainees in the Paediatric Emergency Department for Tonsillitis and Acute otitis media. (7th April 2014) - Ross, AD; Harrison, C; Abrahamson, E
Abstract : Introduction/aims: Overuse of antibiotics has resulted in a rise of resistant strains of bacteria. Prescribing patterns differ between healthcare professionals, however it is difficult to compare attitudes directly due differing environments and patient sets. This study aimed to directly compare the prescribing patterns of General practitioner and Paediatric trainees, working together in the same Urgent Care Centre (UCC) environment with the same patient set, for acute otitis media and tonsillitis. Methods: We conducted a retrospective study of all patients seen in the embedded UCC within our paediatric emergency department, during a 136 day time span, coded as either acute otitis media or tonsillitis. All patients were seen using the Adastra ® computer system, and were randomly assigned to either a GP or paediatric trainee as per our normal urgent care operating system. Patients were excluded that were taking antibiotics at the time of attendance. For each case we recorded whether antibiotics were prescribed, and whether guidelines had been adhered to. Results: There were 349 patients included in the study (252 seen by Paediatric trainees, 97 by GP trainees). Overall, 69.4% (n = 175) of patients cases seen by Paedaitric trainees were administered antibiotics, whilst a significantly greater proportion (94.8%, n = 92) of patients seen by GP trainees were administered antibiotics. These proportion of prescribing was despite guidelines recommending prescription in only 54.2% (n = 189) of cases. There was a significantly greater proportion of cases prescribed antibiotics by GP trainees than Paediatric trainees in both AOM (52.2% n = 35 vs 87.9% n = 29) and tonsillitis (75.7% n = 140 vs 98.4% n = 63). Conclusion: Our study showed all staff working within our UCC over-prescribed antibiotics for upper respiratory tract infections. GPs were significantly more likely to do so than paediatric trainees.